2020
DOI: 10.1186/s40580-020-00228-5
|View full text |Cite
|
Sign up to set email alerts
|

Progressive lysosomal membrane permeabilization induced by iron oxide nanoparticles drives hepatic cell autophagy and apoptosis

Abstract: Iron oxide nanoparticles (IONs) are frequently used in various biomedical applications, in particular as magnetic resonance imaging contrast agents in liver imaging. Indeed, number of IONs have been withdrawn due to their poor clinical performance. Yet comprehensive understanding of their interactions with hepatocytes remains relatively limited. Here we investigated how iron oxide nanocubes (IO-cubes) and clusters of nanocubes (IO-clusters) affect distinct human hepatic cell lines. The viability of HepG2, Huh7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 96 publications
0
15
0
Order By: Relevance
“…For high-quality confocal images, we utilized the brand new high-resolution spinning disk confocal system IXplore SpinSR (Olympus, Tokyo, Japan) [107,108]. The system was equipped with an inverted microscope (IX83; Olympus, Tokyo, Japan) and a spinning disc confocal unit (CSUW1-T2S SD; Yokogawa, Musashino, Japan).…”
Section: Confocal Microscopymentioning
confidence: 99%
“…For high-quality confocal images, we utilized the brand new high-resolution spinning disk confocal system IXplore SpinSR (Olympus, Tokyo, Japan) [107,108]. The system was equipped with an inverted microscope (IX83; Olympus, Tokyo, Japan) and a spinning disc confocal unit (CSUW1-T2S SD; Yokogawa, Musashino, Japan).…”
Section: Confocal Microscopymentioning
confidence: 99%
“…In this study, we demonstrated the integration of PCR with SERS that can detect specific‐cancer mutation at a single gDNA manner. It also does not require complex devices such as microfluidic device and also does not include complex experimental procedures, such as extraction, washing, and isolation 35–37 . It only requires adding blocking DNA and Ag@AuNS after PCR.…”
Section: Discussionmentioning
confidence: 99%
“…The results revealed that the lysosomal pH tended to decrease over time during this process, which is consistent as reported, as lysosomal membrane permeability (LMP) increases during apoptosis, leading to the lysosomal pH change. [121] Dynamic Light Scattering (DLS) is a prevalent, non-invasive technique for characterizing small particles in suspension or the size distribution profile of polymers in solution. DLS allows the characterization of particles in dispersion and permits monitoring of dispersion effects, for example, time and pH effects on colloid stability.…”
Section: Monitoring Apoptosismentioning
confidence: 99%